Pleistocene Eider Duck (Somateria cf. mollissima) from Champlain Sea Deposits near Shawinigan, Québec - Harington, C.; Occhietti, S. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1980)
Most of a pelvic bone of a large eider duck (Somateria cf. mollissima) was collected in place in a unit of stratified clay and sandy silt near Shawinigan, Québec. The fossil is important because it is the first bird specimen from Champlain Sea deposits to be identified to the generic level. Evidently the duck died and was deposited near the northern shore of the Champlain Sea a few hundred years before the sea drained. A sample from a bed of large, marine mollusc shells (Mya arenaria) found in place just above the eider duck fossil yielded a radiocarbon date of 10 300 ± 100 years BP.